Electrochemical and adsorption studies of a carboxylic acid-modified aluminium aminoterephthalate framework (H2N-MIL-53) with heterogeneous catalysis applications - Peens, Frederick Hermanus (University of the Free State, 2015)
The Metal Organic Framework (MOF), MIL-53(Al) and its amine functionalised analogue, amino- MIL-53(Al) were synthesized in good yields (57 - 87%) and were employed as solid, porous support systems for the intrusion of ferrocene (Fc), ferrocenecarboxylic acid (FcCOOH) and a series of carboxylic acids with increasing chain length. The intrusion of HCOOH, CH3COOH, CH3CH2COOH, CH3(CH2)2COOH and Fc into MIL-53(Al) was done by a newly developed Incipient Wetness Impregnation (IWI) method: after evacuation of the porous MOF, the highvacuum was maintained while covering the MOF with the impregnation solution, where after the vacuum was relieved and the solution allowed to intrude into evacuated the pores of the material under atmospheric pressure. The effectiveness of this IWI method was demonstrated by the maximum load of 0.80 HCOOH molecules per unit cell, achieved for HCOOH@MIL-53(Al). Time-resolved intrusion studies, using CH3(CH2)2COOH and FcCOOH, both showed that a maximum load of impregnated material was reached after 16 h of intrusion into amino-MIL-53(Al). An amidation reaction after intrusion resulted in covalent attachment of the acids to the framework structure. In the cases of CH3(CH2)2COOH and FcCOOH, a maximum of 20% and 12% (w.r.t. the total number of available amine groups in amino-MIL-53(Al)) respectively, were covalently bound through amide bonds to the amino-MIL-53(Al) structure, to give CH3(CH2)2CONH-MIL-53(Al) and FcCONH-MIL-53(Al). Using a 16 h intrusion period, high loadings of ferrocene, 7.59 mass% in Fc@MIL-53(Al) and 11.02 mass% in Fc@amino-MIL-53(Al), were achieved during IWI, as determined with TGA. A newly developed solid state Cyclic Voltammetry technique, performed on the Fc-containing framework structures, Fc@MIL-53(Al) as well as Fc@amino-MIL-53(Al) and FcCONH-MIL- 53(Al) showed well defined redox couples at E0' = 1, -13 and -71 mV (vs. Fc/Fc+) respectively. Chemically bound Fc (in FcCONH-MIL-53(Al)) is thus easier to oxidise than free Fc in the channels of the framework structure. Electrochemical reversibility was found in the cases of Fc@amino-MIL-53(Al) and FcCONH-MIL-53(Al), with ?Ep = 57 and 21 mV respectively, whereas Fc@MIL-53(Al) (?Ep = 77 mV) showed quasi-reversibility. All three compounds showed limited chemical reversibility (0.6 ≤ ipc/ipa ≤ 0.7), due to ionic material leaving the analyte during measurement.

Die Metaal Organiese Netwerk (MOF), MIL-53(Al) en sy amiengefunksionaliseerde analoog, amino-MIL-53(Al), is met goeie opbrengste (57 - 87%) gesintetiseer en is gebruik as vaste, poreuse draersisteme vir die intrusie van ferroseen (Fc), ferroseenkarboksielsuur (FcCOOH) en 'n reeks karboksielsure met toenemende kettinglengte. Die intrusie van HCOOH, CH3COOH, CH3CH2COOH, CH3(CH2)2COOH en Fc in MIL-53(Al) is met 'n nuutontwikkelde vloeistofimpregneringsmetode (Incipient Wetness Impregnation, IWI) gedoen: na evakuering van die poreuse MOF is die sterk vakuum behou, terwyl die MOF bedek is met die impregneringsoplossing, waarna die vakuum verlig is, en die oplossing toegelaat is om die geëvakueerde porieë van die materiaal binne te dring onder atmosferiese druk. Die doeltreffendheid van dié IWI metode is getoon deur die maksimum lading van 0.8 HCOOH molekule per eenheidsel wat vir HCOOH@MIL-53(Al) behaal is. Tydsveranderlike intrusiestudies, met CH3(CH2)2COOH en FcCOOH, het beide getoon dat ‘n maksimum lading geïmpregneerde materiaal bereik word na ‘n 16 h intrusie van amino-MIL-53(Al). ‘n Amidasiereaksie na intrusie, het kovalente binding van die sure aan die netwerkstruktuur tot gevolg gehad. In die geval van CH3(CH2)2COOH en FcCOOH, is ‘n maksimum van 20% en 12% (t.o.v. die totale aantal beskikbare amiengroepe in amino-MIL- 53(Al)) onderskeidelik, kovalent deur amiedbindings aan die amino-MIL-53(Al) struktuur gebind, om CH3(CH2)2CONH-MIL-53(Al) en FcCONH-MIL-53(Al) te gee. Met ‘n 16 h intrusietydperk is hoë ladings van ferroseen, 7.59 massa% in Fc@MIL-53(Al) en 11.02 massa% in Fc@amino-MIL- 53(Al), behaal tydens IWI, soos bepaal met TGA. ‘n Nuutontwikkelde vastetoestand Sikliese Voltammetrietegniek, toegepas op die Fc-bevattende netwerkstrukture, Fc@MIL-53(Al) sowel as Fc@amino-MIL-53(Al) en FcCONH-MIL-53(Al), het duidelike redokskoppels by E0' = 1, -13 en -71 mV (vs. Fc/Fc+) onderskeidelik getoon. Chemies gebonde Fc (in FcCONH-MIL-53(Al)) is dus makliker oksideerbaar as vry Fc in die kanale van die netwerkstruktuur. Elektrochemiese omkeerbaarheid is bepaal in die geval van Fc@amino-MIL- 53(Al) en FcCONH-MIL-53(Al), met ∆Ep = 57 en 21 mV onderskeidelik, terwyl Fc@MIL-53(Al) (∆Ep = 77 mV) kwasi-omkeerbaarheid getoon het. Al drie verbindings het beperkte chemiese omkeerbaarheid (0.6 ≤ ipc/ipa ≤ 0.7) getoon, weens ioniese materiaal wat die analiet tydens meting verlaat het.
Dissertation (M.Sc. (Chemistry))--University of the Free State, 2014
Keywords: Carboxylic acids; Organometallic chemistry; Voltammetry; Amines; Amidation reaction; Metal Organic Framework (MOF); Amine functionality; Incipient wetness impregnation; Time resolved intrusion; Solid state cyclic voltammetry